Performance evaluation of PCBN in end milling of AISI D2 hardened steel under room and preheated machining conditions - Lajis, Mohd Amri; Amin, A. K. M. Nurul; Karim, A.N. Mustafizul; Ginta, Turnad Lenggo (Trans Tech Publications Ltd., Switzerland, 2011)
In this paper, the tool life and tool wear performance of PCBN tool in end milling of AISI D2 hardened steel under room and preheated machining conditions is presented. The tool life and tool wear patterns were examined through tool maker microscope and scanning electron microscope. The results show that the dominant modes of tool wear observed were flank wear, chipping, and notch wear. The main wear mechanisms were abrasion, adhesion, and diffusion promoted by high stress and cutting temperature. It was also observed that longer tool life and higher volume metal removed could be achieved when employing higher preheating temperature.